Development and Validation for the Simultaneous Quantification of Nebivolol Hydrochloride and Hydrochlorothiazide by UV Spectroscopy, RP-HPLC and HPTLC in Tablets - B. Dhandapani; N. Thirumoorthy; D. Jose Prakash (E-Journal of Chemistry)
Simultaneous quantification of nebivolol hydrochloride (NEB-H) and hydrochlorothiazide (HCT) in tablets by UV spectroscopy, RP-HPLC and HPTLC methods were developed. In UV spectrophotometric determination NEB-H and HCT was quantified by simultaneous equation method and absorbance ratio method. In simultaneous equation method absorbance measurements at 282.5 nm (λmax NEB-H) and 271.5 nm (λmax HCT), in absorbance ratio method absorbance measurements at 282.5 nm and 275 nm (iso absorptive point) in methanol. In RP-HPLC method, the drugs were resolved using a mobile phase of 30 mM phosphate buffer (K2HPO4), acetonitrile and triethylamine (50:50:0.1 % v/v) with pH 5.5 using orthophosphoric acid on a C18-ODS- Phenomenex (5 μm, 250 mm x 4.6 mm) column in isocratic mode, Atorvastatin (ATR) used as a internal standard. The retention time of HCT, NEB-H and ATR was 3.31, 4.30 and 6.93 min respectively. In the HPTLC method, the chromatograms were developed using a mobile phase of ethyl acetate: methanol: ammonia (8.5:1:0.5 v/v) on precoated plate of silica gel 60 F254 and quantified by densitometric absorbance mode at 285 nm. The Rf of HCT and NEB-H were 0.21 and 0.41 respectively. Recovery studies of 98.88-102.41%, percentage relative std deviation of not more than 0.8 and correlation coefficient (linearity range) of 0.9954-0.9999 shows that developed methods were accurate and precise. These methods can be employed for the routine analysis of tablets containing NEB-H and HCT.